2017
DOI: 10.1007/s13563-017-0103-1
|View full text |Cite
|
Sign up to set email alerts
|

The local employment impacts of mining: an econometric analysis of job multipliers in northern Sweden

Abstract: The way in which mining contributes to job opportunities in the region where it takes place has become increasingly important for the industry's relations to the local community. The employment impacts of mining are however far from straightforward to assess. Considering these uncertainties about real-life job impacts, it is vital that there are sound assessments of these employment effects. The purpose of this paper is to apply a novel econometric approach to assess mining-induced job multipliers in the empir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 28 publications
5
13
0
Order By: Relevance
“…The figure clearly shows that increases in the number of employees in the mining sector can cause changes in the number of employees in other industries. From the empirical perspective, the employability of the sector is caused by mining-related job multipliers (Moritz et al 2017). Figure 5 illustrates that the mining industry in Australia plummeted significantly in the previous recessions (i.e., in the1970s and 2000s).…”
Section: Descriptions Of Data Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…The figure clearly shows that increases in the number of employees in the mining sector can cause changes in the number of employees in other industries. From the empirical perspective, the employability of the sector is caused by mining-related job multipliers (Moritz et al 2017). Figure 5 illustrates that the mining industry in Australia plummeted significantly in the previous recessions (i.e., in the1970s and 2000s).…”
Section: Descriptions Of Data Sourcesmentioning
confidence: 99%
“…We believe that the stability of the Australian economy could be a reason that has led to only a small percentage change in the shift of mining employment to other sectoral industries. Moritz et al (2017) employ data on the number of employees in selected non-mining sectors and mining sectors covering the relatively recent mining boom period (2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013). Their results show positive statistical relationships between increases in the number of employees in different sectors.…”
Section: Descriptions Of Data Sourcesmentioning
confidence: 99%
“…At the same time, Feyrer et al [83] found that for each million dollars of new production, $80,000 of local wages, and $132,000 in royalties and business income were generated, and that approximately two-thirds of increases persist for up to two-years. In Sweden, Moritz et al [84] found a positive relationship between increases in extractive industry employment and positive changes in employee numbers of other industries, most notably the service sector. While in Australia, Kotey and Rolfe [85] found that not only do extractive regions have higher incomes, but that income is more equitably distributed with more of the workforce employed in technical occupations that are often higher paying.…”
Section: Socio-economic Sustainability Of Miningmentioning
confidence: 99%
“…The Regional economies of Övre Norrland and Mellersta Norrland are dominated by mining and forestry which make up an important domain of specialisation -however, significant effort has recently been placed on diversifying their economies and promoting knowledge-intensive industries as well as into expanding mining-related actives into knowledge-intensive services i.e. technical and environmental consulting activities (Moritz et al, 2017).…”
Section: Employment In Knowledgeintensive Sectors Well Above the Eu28mentioning
confidence: 99%